The faint promise of a distant market: a survey of Belem's trade in non-timber forest products - Shanley, P. (2002)
Increased trade in non-timber forest products (NTFP) has been promoted as one possible means to slow tropical deforestation by increasing the economic value of intact forest. A market surcey of NTFP's occuring in the Capim River basin in eastern Amazonia, Brazil demonstrated that the realitty for many smallholder communities in frontier and remote regions includes chronic transportation difficulties, high variability in fruit production, perishable products and lack of market expertise. In some communities, declining abundance of NTFP's due to logging and fire has resulted in a lack of forest products to even meet subsistence needs. In areas close to cities where transportation is assured and where forest clearing has crowded the natural occurence of some valuable native NTFPs, smallholder who manage and successfully market nativefruit and medicinal species are overcoming there obstacles. In frontier regions and undergoing rapid transformation, however, decline in locally used and regionally marketed NTFPs currently pose detrimental consequences for communities. Findings suggest that an overemphasis on NTFP marketing has diverted attention from local livelihood, resource access and subsistence issues.